2018
DOI: 10.1002/aur.2057
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Pre‐pregnancy Body Mass Index and Gestational Weight Gain in Relation to Autism Spectrum Disorder and other Developmental Disorders in Offspring

Abstract: Most prior studies examining maternal pre‐pregnancy body mass index (BMI) in relation to offspring autism spectrum disorders (ASD) have reported an association, though findings are not uniform and few have also examined gestational weight gain (GWG). Therefore, we examined both in the Study to Explore Early Development, a multi‐site case–control study of children born in 2003–2006. Children identified from clinics, schools, and birth certificates were enrolled at ages 2–5 year and using standardized developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 53 publications
3
53
1
Order By: Relevance
“…*Represents recurrence risk. Figure adapted from 18 with added findings from select reviews and empirical papers: neonatal hypoxia estimate 267 , childhood vaccines 20 , valporate use during pregnancy 268 , parent age estimates 269 , preterm birth estimate 270,271 , maternal obesity estimate 272 , folic acid intake estimate 273 , siblings estimate 274,275 , interpregnancy interval estimate 276 , assisted reproductive technologies estimate 277,278 , pesticide and air pollution estimate 279 , caesarian section estimate 280 . Simplified schematic of the major cellular components of a neural circuit in the cerebral cortex, with a focus on pyramid-shaped glutamatergic excitatory projection neurons.…”
Section: Supportsmentioning
confidence: 99%
“…*Represents recurrence risk. Figure adapted from 18 with added findings from select reviews and empirical papers: neonatal hypoxia estimate 267 , childhood vaccines 20 , valporate use during pregnancy 268 , parent age estimates 269 , preterm birth estimate 270,271 , maternal obesity estimate 272 , folic acid intake estimate 273 , siblings estimate 274,275 , interpregnancy interval estimate 276 , assisted reproductive technologies estimate 277,278 , pesticide and air pollution estimate 279 , caesarian section estimate 280 . Simplified schematic of the major cellular components of a neural circuit in the cerebral cortex, with a focus on pyramid-shaped glutamatergic excitatory projection neurons.…”
Section: Supportsmentioning
confidence: 99%
“…Numerous studies have posited adverse effects of intrauterine inflammatory signals to explain the associations consistently observed between elevated maternal BMI and risk for ASD (52)(53)(54)(55). Here we report that maternal BMI was not associated with APPs in cases or controls measured only a few days after birth, raising the question of whether this particular mechanism to link maternal BMI to risk of ASD is relevant, at least in later pregnancy.…”
Section: Discussionmentioning
confidence: 56%
“…An association between obesity and ASD was found, but not significant AOR: 1.37 (95% CI, 0.98-1.92). 32 Although it was observed that gains between 16 and 20 kg showed an AOR: 1.52 (95% CI, 1.05-2.22) and gains greater than 20 kg an AOR: 1.58 (95% CI, 1.08-2.31). 32 At each 2.3 kg gain the chances of developing autism increased by 6%; with AOR: 1.06 (95% CI, 1.02-1.10).…”
Section: Body Mass Index (Bmi) and Weight Gain During Pregnancymentioning
confidence: 95%
“…32 At each 2.3 kg gain the chances of developing autism increased by 6%; with AOR: 1.06 (95% CI, 1.02-1.10). 32…”
Section: Body Mass Index (Bmi) and Weight Gain During Pregnancymentioning
confidence: 95%